Effects of multi-walled carbon nanotubes with various diameters on bacterial cellular membranes: Cytotoxicity and adaptive mechanisms. (October 2017) - Yang, Fan; Jiang, Qun; Xie, Weiling; Zhang, Ying
Abstract: The effect of multi-walled carbon nanotubes (MWNTs) with different diameters on the destruction degree toward cellular membranes of bacterial has been explored by investigating the viability of bacteria and the change of composition and surface properties in cellular membranes with the exposure of MWNTs. The atrazine degrading bacteria Acinetobacter lwoffii DNS32 (DNS32) is chosen as the model species and Escherichia coli ( E. coli ) and Bacillus subtilis ( B. subtilis ) are selected as the comparison specie. Bacterial viability testing shows that MWNTs with smaller diameters generally display stronger toxicity to bacteria and also influenced by many factors including the electrostatic repulsion between MWNTs and bacteria and bacteria types. Interestingly, bacteria can self-regulate as an adaptive response to the toxicity of MWNTs, notably, DNS32 strain presents the adaptive responses when cultivated with MWNT60-100 through modification of fatty acids in cell membranes, but does not exhibit similar responses when exposed to MWNT10-20 . This result may be related to the interference from MWNT10-20, which exceeds the cellular ability to self-repair. Transmission electron microscopy (TEM) images and flow cytometric analysis of bacteria exposed to MWNTs reveal that the destruction of cell membrane in the DNS32 strain is more serious than that in the B. subtilis, indicating that electrostatic repulsion between the material and bacteria leading to the decrease of direct contact may be the primary factor that reduces the impacts from MWNTs. Highlights: MWNTs with various diameters have different destruction degree to cell membranes. Bacteria can self-regulate as an adaptive response to the toxicity of MWNTs. Electrostatic repulsion can greatly reduces the impact of MWNTs to bacteria.